Toughening of epoxy-based hybrid nanocomposites. (5th August 2016) - Carolan, D.; Ivankovic, A.; Kinloch, A.J.; Sprenger, S.; Taylor, A.C.
Abstract: The microstructure and fracture performance of an epoxy resin cured with an anhydride hardener containing silica nanoparticles and/or polysiloxane core-shell rubber (CSR) nanoparticles were investigated in the current work. The effect of adding a reactive diluent, i.e. hexanediol diglycidylether, to the epoxy resin was also investigated. The fracture energy of the neat (i.e. unmodified) epoxy polymer increased slightly from 125 J/m 2 to 172 J/m 2 due to the addition of 25 wt% of the reactive diluent to the epoxy. The fracture energy of the unmodified epoxy polymer increased to 889 J/m 2 when 20 wt% of the CSR nanoparticles were added to the epoxy without any reactive diluent being present. However, the results show that the increase in fracture energy due to the addition of the CSR nanoparticles particles was much more marked in the case when 25 wt% of the reactive diluent was present, e.g. an increase to 1237 J/m 2 with the addition of 16 wt% of CSR nanoparticles. Furthermore, while the subsequent addition of silica nanoparticles, to give hybrid epoxy polymer nanocomposites, i.e. which contained both silica and CSR nanoparticles, produced only modest increases in the fracture energy in the case of the epoxy with the reactive diluent additive present, some synergistic effects on the toughening were noted. No significant improvements in toughness were found for the hybrid epoxy polymer nanocomposites without reactive diluent. The measured toughness of the hybrid materials can be related to the degree of dispersion of both nanoparticle phases in the epoxy polymer matrix. The toughening mechanisms were identified and the experimentally measured values of toughness were in good agreement with modelling studies. Graphical abstract: Highlights: Epoxy nano composites are fabricated using silica nanoparticles and core shell rubber. Fracture toughness of epoxy hybrid nanocomposites depends on nano morphology. Shear banding and void growth are identified toughening mechanisms. Fracture toughness can be predicted analytically.